PERISTILAHAN DALAM BUBOREH PADA MASYARAKAT DAYAK BIH NANGEH - Leonardo, Fransiskus; Patriantoro, Patriantoro; Amir, Amrian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractBuboreh is a traditional medicine that is in the community of Dayak Bih Nangeh. This research was conducted in the estuary of the River, the village of Ilai, Beduai Subdistrict, Sanggau. Problems in the study is how the form of terminology in the Buboreh, the meaning of the lexical meaning of the cultural and the resulting text form as a supplement language learning materials Indonesia with scope on pre-implementation, the implementation and post-implementation. This research was done using descriptive methods with qualitative form. Techniques of data collection, use, fishing techniques, engineering, proficient at first, and record. Based on the results of the analysis, this research managed to muster 79 data terminology in a Buboreh comprising 48 lexical meanings of terminology data, 19 cultural meanings of terminology data, 8 data terminology pay custom, 4 data terms of lingual units the form of the word derivative                                                                            Keywords: terminology, buboreh, lexical meaning, cultural meaning